ACTUALIZATION OF DERADICALIZATION AND DISENGAGEMENT IN THE DEVELOPMENT OF TERRORIST NAPI IN INDONESIA - Fadillah Mursid (Polteknik Ilmu Pemasyarakatan, 2018)
The issue of terrorism in Indonesia is one of the main problems of this nation that needs to get serious attention from the government. A series of incidents of terror during this time indicates an unresolved problem in countering terrorism. Based on the problem, the focus of this research study is how the guidance of terrorist prisoners in LP, then how the concept of deradicalization and disengament as an effort penagebulnyanya, and how to actualize the two concepts? This research including the kind of research normative law, while specification this research is descriptive analytical Legal material used in covering primary, secondary, and tertiary legal materials. The collection of legal materials in this paper is done by doing literature research and document studies. The main approach is doctrinal. Based on the results of research can be concluded that First, the concept of terrorism punishment aims to realize the ultimate goal of coaching, namely rehabilitation and resosialisasi offenders, even to the suppression of crime (suppression of Crime). Second, Deraikalisasi sebgai efforts to eliminate radical understanding can be done in several ways namely, Rehabilitation, reedukasi, resosialisasi, and reintegration. Disengagement aims to break the relationship of former terrorist prisoners not to join their former group. Third, the approach used in actualizing both programs is First Strategy, refining the strategy focused on law enforcement and balanced with prevention and protection efforts to obtain comprehensive results. The second strategy is to utilize the full potential of the state's resources through the involvement of related elements in the superstructure, infrastructure and substructure. The third strategy is to synergize all the sectoral lines in counterterrorism that have been done by various components and not fragmented. For concrete steps in actualizing it there are two things that must be done, namely improving the quality of human resources that have a good understanding of the Prisoner, and classification of inmates as an effort to facilitate in coaching.